Seeking evidence-based policy solutions to poverty and malnutrition in Bangladesh: Highlights from the Policy Research and Strategy Support Program 2010-2014 - Ahmed, Akhter (International Food Policy Research Institute, 2014)
Food labelling is costly. Food labelling is often demanded with the introduction of new food products such as genetically modified (GM) food. If consumers do not have trust in the label, scarce resources are wasted. This paper investigates factors affecting the trust in food labels among Ugandan consumers. The results suggest that older, less-educated individuals of smaller household sizes and with trust in government institutions have more trust in food labels. Other factors were also found to be important. The government has to consider those differences in consumer trust when designing a GM labelling policy.